Influence of thyroid gland in women with abnormal uterine bleeding in reproductive age group - Marimuthu, Kavitha; Loganathan, Malarvizhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal Uterine Bleeding is a common complaint encountered in Gynaecology OPD. It occurs in 9-14% of women from Menarche to Menopause affecting quality of life imposing financial burden. Thyroid dysfunction causes broad spectrum of reproductive disorders from abnormal sexual development, menstrual irregularities, infertility and premature menopause. Thyroid disorders are 10 times more common in women and increased prevalence of thyroid disorders in women is possibly due to auto immune nature. Methods: This Prospective study population consisted of 250 women attending the Gynaecology Outpatient Clinic, in Government Dharmapuri Medical College Hospital, with complaints of bleeding problems during menstruation in the age group of 18 to 45 years. Results: Of 250 cases of abnormal uterine bleeding in reproductive age group attending the outpatient department about 68 cases have thyroid dysfunction. The common thyroid dysfunction in our study was hypothyroidism which comprises about 15.6% similarly other thyroid dysfunction are hyperthyroidism in 7.2% and subclinical hypothyroidism in 3.2% and subclinical hyperthyroidism 1.2%. Conclusions: It brings into focus the increased incidence of hypothyroidism among women with menorrhagia and amenorrhea. And increased incidence of hyperthyroidism in women with oligomenorrhea. Early detection by selective screening and specific pharmacotherapy for subclinical thyroid disease early in the course of the disease will prove to be a superior alternative to surgical treatments like hysterectomy.